Implementasi Kurikulum Merdeka Tema “Aku Sayang Bumi” Pada Anak Usia Dini di Ra Al Jihad Malang - Rochmah, Ainur; Mupi Anisah; Rahmi; Laila Nur Fitriah (Institut Agama Islam Negeri Madura, 2024)
This research was conducted to determine the role of teachers/child assistants in implementing and the influence of implementing a merdeka curriculum system with the theme